Structural basis for inhibition of human PNP by immucillin-H - de Azevedo, W. F.; Canduri, F.; dos Santos, D. M.; Pereira, J. H.; Dias, MVB; Silva, R. G.; Mendes, M. A.; Basso, L. A.; Palma, Mario Sergio [UNESP]; Santosce, D. S. (Elsevier B.V., 2003)
Purine nucleoside phosphorylase (PNP) catalyzes the phosphorolysis of the N-ribosidic bonds of purine nucleosides and deoxynucleosides. PNP is a target for inhibitor development aiming at T-cell immune response modulation. This work reports on the crystallographic study of the complex of human PNP-immucillin-H (HsPNP-ImmH) solved at 2.6 Angstrom resolution using synchrotron radiation. Immucillin-H (ImmH) inhibits the growth of malignant T-cell lines in the presence of deoxyguanosine without affecting non-T-cell tumor lines. ImmH inhibits activated normal human T cells after antigenic stimulation in vitro. These biological effects of ImmH suggest that this agent may have utility in the treatment of certain human diseases characterized by abnormal T-cell growth or activation. This is the first structural report of human PNP complexed with immucillin-H. The comparison of the complex HsPNP-ImmH with recent crystallographic structures of human PNP explains the high specificity of immucillin-H for human PNP. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: PNP; synchrotron radiation; Structure; immucillin-H; drug design